Analysis Of The Influence Of Job Satisfaction, Work Discipline And Organizational Culture On Performance Of State Civil Apparatus In Ministry Offices - Syamsul Hadi; Sarwo Hakim; Kiki Setyawati; Siti Annisa Wahdiniawati; Muhammad Syafri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
With job satisfaction acting as an intervening variable, the purpose of this study is to ascertain if corporate culture and work discipline have an impact on employee performance. All of the participants in this study are employees. Saturated sampling or complete sampling are the sampling criteria used in this study. There were 100 samples used in this investigation. This kind of study data is included in quantitative data. Literature reviews, questionnaires, and interviews were employed by researchers. The existence of a link between latent variables and the indicators that make them up is known as the measurement model. The instrument's validity and dependability are evaluated using this model. A model that links apparent and latent variables is called the structural model. We use R2 as the dependent construct in PLS to assess inner capital. T-statistics and Patrial Least Square (PLS) were utilized in this study's data analysis. These conclusions can be drawn from the data analysis results: Job satisfaction and organizational culture characteristics are unaffected. The work discipline variable has an impact on job satisfaction. There is a relationship between employee performance and organizational culture. Employee performance is impacted by the work discipline variable. Employee performance and job satisfaction are impacted. Through work happiness, there is a relationship between company culture and employee performance. Workplace discipline affects employee performance through job satisfaction.